EFFECT OF MIFEPRISTONE AND CABERGOLINE IN THE TERMINATION OF PREGNANCY IN BITCHES - CHAUDHARI, R K; SUTARIA, T V; CHAUDHARI, C F; NAKHASHI, H C; SUTHAR, B N (The Indian Journal of Animal Reproduction, 2022)
Termination of unwanted pregnancy is one of the most common requests from dog owners. Three bitcheswerepresented to the clinics with a history that the bitches were mated 30 days back and were diagnosed as pregnant withhelp of ultrasonography. On the request of owner, pregnancy termination was carried out by using mifepristone @2.5mg/kg body weight, orally twice daily with cabergoline @ 5 μg/Kg body weight daily for 4 days. All the three bitcheswere aborted within 6 days without any side effects.
Keywords: Mismating; cabergoline; mifepristone; bitch; pregnancy termination